Co-innovation in the coffee producer-supplier relationship: the case of the department of Meta (Revista "Boletín el Conuco", 2022)
Recently, the study of commercial relations from the relational marketing paradigm has been embraced in agribusiness as it seeks to understand the importance of commercial relations between producer and supplier. Thus, the purpose of this article was to characterize the behavior of the different dimensions of quality from the commercial relationship and its variables. The methodology had a descriptive approach of a conclusive type, with a functionalist approach. To achieve this, a general documentary review of the coffee sector in the department of Meta was carried out, along with 41 surveys of producers and 3 interviews with supply chain coordinators. The findings were capitalized on quality, innovation and co-innovation between coffee producers and suppliers.
Keywords: co-innovation; coffee; commercial relation; producer; supply chain